Tracing the Changing Measures of Unemployment in Dutch Unemployment Statistics 1900-1940 - Peter Rodenburg (Tinbergen Institute, 2001)
In the period before the second World War, the Dutch Bureau of Statistics had developed two sets of indicators ofunemployment in the Netherlands. One was based on statistical data of unemployment insurance funds of tradeunions and the other one on statistical data of labour exchanges. This paper explores the historical development ofthese indicators and tries to interpret their meaning over the period 1900 – 1940. In this period variousbreakpoints can be found in which the interpretation of the indicators had changed. Finally, in order to get insightin the reliability of the two measures of unemployed they are compared to each other for a specific data, namelythe 31st of December 1930, when a Dutch census was held.
Keywords: J; N; 330; Statistics of unemployment; measurement; unemployment; labour movement 1900-1940; Arbeitslosigkeit; Messung; Statistische Methode; Niederlande